Improving Understanding In Preventing Stunting In The First 1,000 Days Of Life: Peningkatan Pemahaman Dalam Mencegah Kejadian Stunting Pada 1000 Hari Pertama Kehidupan - Anne Rufaridah; Asmita Dahlan; Wuri Komalasari; Sri Marlia; Rika oktariantiaskar (Journal of Community Service and Application of Science, 2022)
The World Health Organization (WHO) defines stunting as a state of very short stature that exceeds a deficit of 2 SD below the median length or population height which is an international reference (Trihono, et al., 2015). Stunting is closely related to the first 1000 days of life (HPK) period. . The 1000 HPK period is an important period or a golden period for growth and development. 1000 HPK starts from pregnancy until the child is 2 years old. 1000 HPK is called the Window of Opportunity because during this period organ systems experience a very rapid increase in growth and development. Based on data from Basic Health Research (Riskesdas), the prevalence of stunting in Indonesia fluctuated, namely in 2007 it was 36.8%, 35.6% (2010), 37.2% (2013), and 30.8% (2018). Based on Riskesdas, the prevalence of stunting in West Sumatra fluctuated, namely in 2007 it was 36.5%, 32.7% (2010), 39.2% (2013), and 29.9% (2018). This community service activity is carried out in Kelurahan Andalas Padang by providing counseling to mothers who have toddlers. This activity was carried out on June 30, 2022.1000 First Day